Comparison of Mean Analgesia Consumption for Postoperative Pain with Single Dose of Preoperative Oral Gabapentin versus Placebo in Patients Undergoing Surgery Under General Anesthesia - Iram Shahzadi, Muhammad Idrees, Maryam Sultana, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative pain management aims to alleviate discomfort, promote early recovery from surgery, shorten hospital stays, and increase patient satisfaction. Multimodal treatment is the best method for perioperative pain management since it reduces the requirement for opioids. For postoperative pain, the anticonvulsant medicine gabapentin is safe and effective. Objective: To compare mean analgesia consumption for postoperative pain with single dose of preoperative oral gabapentin versus placebo in patients undergoing surgery under general anesthesia. Design of the Study: Descriptive case series. Place and Duration of Study: This study was carried out at Department of Anesthesia, Combined Military Hospital, Muzaffarabad from 6-1-2018 to 6-7-2018. Patients and Methods: From the operation theatre, 60 patients who met the criteria for selection were selected. Patients were then divided into two groups at random using the lottery method. Patients in group A received gabapentin. Oral placebo capsules were administered to group B one hour prior to surgery. All patients received anaesthesia. The post-anesthesia care unit was transferred with the patients. During the first 12 hours, pain and total morphine consumption were noted. This entire data was entered into a proforma. The SPSS version 21 application was used to enter and analyze the data. Using an independent sample t-test, the mean analgesia consumption of the two groups was compared. P-values lower than 0.05 were considered significant. Results of the Study: Patients in the gabapentin group have mean age of 42.30±6.90 yrs compared to 43.50±8.48 yrs in the placebo group. In the gabapentin group, there were 16 (53.3%) males and 14 (46.7%) women, while in the placebo group, there were 50% males and 50% women. In the gabapentin group, the mean BMI was 26.80±4.26 g/m2, while in the placebo group, it was 26.97±2.37 g/m2. After 12 hours, the mean pain score was 2.43 0.82 in the gabapentin group and 3.97±1.56 in the placebo group. The difference was statistically significant (p 0.05).The mean analgesia consumed in a 12-hour period was 10.53±1.96mg/kg in the gabapentin group versus 13.10±2.25mg/kg in the placebo group. The difference was significant statistically (p<0.05).. Conclusion: It was shown that a single dose of gabapentin was effective in reducing the postoperative pain and amount of analgesic consumption required during the postoperative period. Keywords: General Anesthesia, Gabapentin, Postoperative Pain, Placebo, Opioids, Morphine, Analgesia Consumption,